Assessment of loading phase change material into net meter building to boost excess electricity generation. (15th July 2022) - Abdalla, Ahmed N.; El-Shafay, A.S.; Ju, Yongfeng; El-Rahman, Magda Abd; Nazir, Muhammad Shahzad; Sharifpur, Mohsen
Abstract: In this study, two techniques were used to reduce electricity demand in the building. In the first technique, PCM of RT18 was injected with 5 cm thickness into the walls and roof. This material reduced the energy exchanged from the building and led to 24.76% less electricity usage by the chiller to adjust the building temperature at 25 °C and 28 °C in occupancy and non-occupancy hours. This PCM led to electricity saving by 19, 945 kWh/year. In the next step, photovoltaic cells were added to the PCM-filled roof. The PV installed in the roof generated electricity in the range of 4200–9500 kWh. When installed on a PCM-equipped roof, the photovoltaic cells reduced the intensity of the radiation and, as a result, allowed less thermal energy to enter the building through the roof. Consequently, electricity demand dropped by 5.5%. Eventually, the installation of photovoltaic cells resulted in electricity saving by 84, 351 kWh/year due to the electricity generation and 3294 kWh/year owing to a decrease in radiation intensity over the roof. Highlights: Two techniques of adding PCM and mounting PV on roof were used to reduce electricity demand. PCM reduced the energy exchanged from the building and led to 24.76% less electricity usage. PCM led to electricity saving by 19, 945 kWh/year. Mounting PV resulted in electricity saving by 84, 351 kWh/year due to the electricity generation.